Soil Phosphorus Availability Impacts Chickpea Production and Nutritional Status in Tropical Soils - Delfim, Jorge; Moreira, Adônis; Moraes, Larissa A. C.; Silva, Juliana F. [UNESP]; Moreira, Pedro A. M. [UNESP]; Lima Filho, Oscar F. (Springer Nature, 2024)
Chickpea is an excellent source of protein for human and animal consumption; however, the lack of phosphorus (P) limits their development and grain yield, mainly in tropical soils with high P adsorption capacity. However, information about the P availability in Oxisols for chickpea production is limited. This study aimed to evaluate the effect of P rates on yield components, soil P availability, and the nutritional status of plants grown in two contrasting soil types. The experiment was conducted under greenhouse conditions in a completely randomized 2 × 4 factorial arrangement with two soil types (sandy-clay and sand texture) and four P rates (0, 50, 100, and 200 mg kg− 1) of triple superphosphate, each with five replicates. The P rates increased the grain yield (R2 = 0.67, p ≤ 0.05) in sandy-clay texture soil and (R2 = 0.87, p ≤ 0.05) in sand texture soil. Additionally, all the yield components showed positive effects by P rates addition, but, among the two soil types, the sandy-clay soil showed the highest increases in all analyzed yield components. The P concentration in the grains was significantly enhanced by P rate application for both soil types, whereas leaf P concentration only increased in the sand soil. Additionally, P use efficiency (PUE) ranges from 4.62 to 35.52% of chickpea grown under sandy-clay soil, and from 22.0 to 34.30% under sand soil. Furthermore, the leaf concentrations of N, P, K, Ca, S, Fe, Mn, Cu, and Zn were influenced by P rate and soil texture. The P rates application increased the available P in the soil in both sandy-clay and sand soils, irrespective of the extractants (Mehlich-1 and resin) used. P soil availability, plant P uptake and chickpea growth and yield are influenced positively or negatively by P rates and the soil texture. The positive and negative effects observed in this study demonstrate the significance of improved P management for the yield and nutritional quality of chickpeas in tropical soil conditions. Further, the management should consider the soil type and improvements in PUE to increase yield and prevent P loss.
Keywords: Cicer arietinum; Nutritional status; P Extractant; Phosphorus use efficiency; Yield components